Dominant Ideologies, Neoliberal Jesuses, and the Academic Study of Religion - Tite, Philip L. (Bulletin for the study of religion, 2014)
Editor's introduction to the issue. This issue includes a panel on James Crossley's book, Jesus in an Age of Neoliberalism (with responses by Justin Tse, Ian Henderson, and Roland Boer as well as a reply by James Crossley). This issue also includes an article on Pauline pseudepigraphy by Gregory Fewster and a pedagogical article by Erica Martin on effectively teaching extroverted and introverted students.